Research on the Safety Assessment of Corbel Beams of Reservoir Radial Gates Based on Real States - Jiayi Lin; Ronglu Wang; Yan Zhao; Yuelin Sun (Applied Sciences, 2023)
The radial gate corbel beam is a kind of gate support structure more often used in large and medium-sized reservoirs, but the current corresponding structural design code does not give a review calculation method for it. Because there are obvious differences between a corbel and a corbel beam in structural form and force, if the corbel beam is just simplified in the calculation as a corbel structure, it can easily lead to misjudgment of insufficient bearing capacity. This misjudgment has a significant impact on later safety assessment, danger removal, and reinforcement. Currently, there are limited studies available on the internal stress distribution of the corbel beam. In this study, taking the danger removal and reinforcement of the radial gate beam of a medium reservoir in Beijing as an example, the concrete quality of the dam was tested by the core drilling method, and two safety review methods of the corbel beam for different types of reservoirs were proposed in combination with the Code for Design of Hydraulic Concrete Structures (SL191-2008). Then, three different types of calculation model were established by the method of theoretical mechanics calculation and finite element simulation. Combined with the safety test data, the stress state of the combined stress structure of the corbel beam and gate pier under the real state was analyzed and the safety evaluation was carried out. The calculation results of these two corbel beam safety review methods were respectively reduced by 32% and 47% compared with the current calculation method. Engineering practice has proved the rationality of the two safety evaluation methods proposed in this paper, which can provide a certain reference for similar engineering reinforcement.